1998
DOI: 10.1183/09031936.98.12061264
|View full text |Cite
|
Sign up to set email alerts
|

Does arousal frequency predict daytime function?

Abstract: Patients with the sleep apnoea/hypopnoea syndrome (SAHS) suffer from excessive daytime sleepiness [1,2], cognitive decrements [3,4] and decreased psychological well-being [5]. These daytime effects lead to an increased risk of vehicle accidents [6], work inefficiency [7] and poor social relationships [7]. Previous correlational studies [3,5,8,9] have looked at possible causative relationships between the nocturnal features of SAHS and daytime function. However, there is still controversy as to what extent thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
2
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 39 publications
6
74
2
3
Order By: Relevance
“…This shows that the severity of OSAS as evaluated by conventional nocturnal measures and the extent of daytime impairment are not necessarily related, as demonstrated recently in patients with OSAS [28,31], and underlines the necessity to observe not only the physiological disturbances of OSAS but also the impact on the patients' quality of life.…”
Section: Discussionsupporting
confidence: 57%
“…This shows that the severity of OSAS as evaluated by conventional nocturnal measures and the extent of daytime impairment are not necessarily related, as demonstrated recently in patients with OSAS [28,31], and underlines the necessity to observe not only the physiological disturbances of OSAS but also the impact on the patients' quality of life.…”
Section: Discussionsupporting
confidence: 57%
“…The mean sleepiness score of UARS patients was 8.1 ¡ 3.6 (range 1-16), while the mean score of OSAS patients was 10.6 ¡ 5.2 (range [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. There were 16 OSAS and three UARS patients with an ESS score w10, which was defined as the upper point of normal range of sleepiness [33].…”
Section: Resultsmentioning
confidence: 99%
“…apnoea/hypopnoea [5][6][7][8] or hypoxaemia [7][8][9]), have been postulated as the main causes of EDS. In addition, reduction in the restorative nature of sleep by arousals [10][11][12], fragmentation of sleep [13,14], a lack of slow-wave sleep [15] and a reduction in total sleep time (TST) [16], have all been suggested as possible causes of EDS.…”
mentioning
confidence: 99%
“…Although counterintuitive, this is not surprising as previous studies in both adults 17 and children [18][19][20] have shown a poor relation between polysomnographic parameters and neurocognitive/ behavioral outcomes. This may be because of the complex interplay of the many polysomnographic variables and multiple other factors that affect behavior, or it may be that the effect of OSAS on behavior reflects a threshold rather than a linear dosing effect.…”
Section: Discussionmentioning
confidence: 84%